2020
DOI: 10.18632/aging.103323
|View full text |Cite
|
Sign up to set email alerts
|

The effect of swimming exercise and diet on the hypothalamic inflammation of ApoE-/- mice based on SIRT1-NF-κB-GnRH expression

Abstract: A high-fat diet and sedentary lifestyle could accelerate aging and hypothalamic inflammation. In order to explore the regulatory mechanisms of lifestyle in the hypothalamus, swimming exercise and diet control were applied in the high-fat diet ApoE-/-mice in our study. 20-week-old ApoE-/-mice fed with 12-week high-fat diet were treated by high-fat diet, diet control and swimming exercise. The results showed that hypothalamic inflammation, glial cells activation and cognition decline were induced by high-fat die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…According to animal studies, exercise, such as running, seems to reduce diet-induced hypothalamic inflammation in rodents [ 197 ]. In line with these results, swimming and diet can diminish not only hypothalamic inflammation, but also memory decline in an APOE4 mice model [ 198 ]. In addition, dietary options can improve hypothalamic inflammation.…”
Section: Potential Prevention Of Mood and Cognitive Disorders By Tmentioning
confidence: 58%
“…According to animal studies, exercise, such as running, seems to reduce diet-induced hypothalamic inflammation in rodents [ 197 ]. In line with these results, swimming and diet can diminish not only hypothalamic inflammation, but also memory decline in an APOE4 mice model [ 198 ]. In addition, dietary options can improve hypothalamic inflammation.…”
Section: Potential Prevention Of Mood and Cognitive Disorders By Tmentioning
confidence: 58%
“…Our results also suggested that the combined diet induced differential neuro-inflammatory responses, with the activation of NLRP3 in young mice, while both the activation of NF-κB and NLRP3 might be involved in regulating neuro-inflammation for middle-aged mice; and we further demonstrated that voluntary exercise could alleviate combined diet induced neuro-inflammation, which is consistent with previous studies. 16,34 Additionally, circadian system dysfunction has also been proposed to play a key role in cognitive defects; also neuroinflammation is closely related with the disruption of circadian time keeping during cognitive impairment. 21,22 In particular, it has been reported recently that Rev-erbα repressed transcription of p65 (a subunit of NF-κB) and indirectly repressed NLRP3 via the NF-κB pathway.…”
Section: Neuro-inflammation and Circadian Clockmentioning
confidence: 99%
“…Within the hypothalamus, Sirt1 mRNA is highly expressed in the arcuate, ventromedial, dorsomedial and paraventricular nuclei. Its activity within the brain has been linked to brain aging, neuroprotection against oxidative stress, neuroinflammation and ischemic injury, central control of energy homeostasis, modulation of circadian clock, and neuroendocrine functions [35,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Sirt1 expression regulates both the fate of neural stem cells (NSCs) during development and the activity of neurons through several pleomorphic pathways [63].…”
Section: Sirt1 Activity In the Brainmentioning
confidence: 99%
“…Deletion of Sirt1 in hypothalamic Agouti-related peptide-expressing neurons creates a pro-inflammatory environment, with enhanced effector T-cell activity and decreased regulatory T-cell function [58] Hypothalamic inflammation, glial cells activation and learning and memory impairment were alleviated by swimming exercise plus diet control, which was related to the increasing expression of Sirt1 [59] Psychiatric disorders Several Sirt1single nucleotide polymorphisms were over-represented in patients with depression and anxiety disorders [60] Sirt1 levels correlates with anxiety and exploratory drive and is mechanistically linked with serotonin levels in the brain [61] Cocaine or morphine administration increases Sirt1 expression in the nucleus accumbens, a brain region that regulates motivation and reward [62] Taken together, dysfunction in specific neuronal populations within the hypothalamus is related to physiological or pathological brain aging. The dysregulation of nutrient sensing, impaired neuronal communication network, NSC exhaustion, impaired repair mechanisms and alterations in the epigenetic machinery have age-related consequences on the decline in energy metabolism, hormone regulation, circadian rhythm and reproduction [74].…”
Section: Immunitymentioning
confidence: 99%